Holding all the ACEs. Issue 7 (4th September 2020) - Thompson, Angus
Abstract : A lot has happened since captopril, the first ACE inhibitor, was launched in the early eighties. Here, Angus Thompson reflects on the wide range of renin‐angiotensin system (RAS)‐blocking drugs that have come to the market since, and how their use has evolved.